Assessing the Likelihood of Having a Regular Health Care Provider among African American and African Immigrant Women - Ahad, Fatema Binte (Ethn Dis, 2019)
OBJECTIVE: Immigrants, especially refugees, face unique barriers to accessing health care relative to native born Americans. In this study, we examined how immigration status, health, barriers to access, and knowledge of the health care system relate to the likelihood of having a regular health care provider. METHODS: Using logistic regression and data from a community-based participatory study, we estimated the relative likelihood that an African immigrant woman would have a regular health care provider compared with an African American woman. RESULTS: Immigrant status remains a powerful predictor of whether a woman had a regular health care provider after controlling for covariates. African immigrants were 73% less likely to have a regular health care provider than were otherwise similar African American women. CONCLUSION: Expanding health care educational efforts for immigrants may be warranted. Future research should examine how cultural beliefs and time in residence influence health care utilization among US immigrants.